Hemodiafiltration with endogenous reinfusion for uremic toxin removal in patients undergoing maintenance hemodialysis: a pilot study - Renhua Lu; Yan Fang; Wangshu Wu; Xiaojun Zeng; Tingting Liu; Yue Qian; Yuanyuan Xie; Yijun Zhou; Leyi Gu (Renal Failure)
Objective To delineate the efficacy and safety profile of hemodiafiltration with endogenous reinfusion (HFR) for uremic toxin removal in patients undergoing maintenance hemodialysis (MHD).Methods Patients who have been on MHD for a period of at least 3 months were enrolled. Each subject underwent one HFR and one hemodiafiltration (HDF) treatment. Blood samples were collected before and after a single HFR or HDF treatment to test uremic toxin levels and to calculate clearance rate. The primary efficacy endpoint was to compare uremic toxin levels of indoxyl sulfate (IS), λ-free light chains (λFLC), and β2-microglobulin (β2-MG) before and after HFR treatment. Secondary efficacy endpoints was to compare the levels of urea, interleukin-6 (IL-6), P-cresol, chitinase-3-like protein 1 (YKL-40), leptin (LEP), hippuric acid (HPA), trimethylamine N-oxide (TMAO), asymmetric dimethylarginine (ADMA), tumor necrosis factor-α (TNF-α), fibroblast growth factor 23 (FGF23) before and after HFR treatment. The study also undertook a comparative analysis of uremic toxin clearance between a single HFR and HDF treatment. Meanwhile, the lever of serum albumin and branched-chain amino acids before and after a single HFR or HDF treatment were compared. In terms of safety, the study was meticulous in recording vital signs and the incidence of adverse events throughout its duration.Results The study enrolled 20 patients. After a single HFR treatment, levels of IS, λFLC, β2-MG, IL-6, P-cresol, YKL-40, LEP, HPA, TMAO, ADMA, TNF-α, and FGF23 significantly decreased (p < 0.001 for all). The clearance rates of λFLC, β2-MG, IL-6, LEP, and TNF-α were significantly higher in HFR compared to HDF (p values: 0.036, 0.042, 0.041, 0.019, and 0.036, respectively). Compared with pre-HFR and post-HFR treatment, levels of serum albumin, valine, and isoleucine showed no significant difference (p > 0.05), while post-HDF, levels of serum albumin significantly decreased (p = 0.000).Conclusion HFR treatment effectively eliminates uremic toxins from the bloodstream of patients undergoing MHD, especially protein-bound toxins and large middle-molecule toxins. Additionally, it retains essential physiological compounds like albumin and branched-chain amino acids, underscoring its commendable safety profile.